Human papillomavirus vaccine series completion: Qualitative information from providers within an integrated healthcare organization. Issue 30 (24th June 2016) - Hudson, Sharon M.; Rondinelli, June; Glenn, Beth A.; Preciado, Melissa; Chao, Chun
Abstract: Objective: This qualitative study aimed to identify doctors' and nurses' perceptions of patient-, provider-, and system-level factors associated with human papillomavirus (HPV) vaccine completion that may be targets for intervention. Methods: We analyzed data from 61 qualitative interviews with pediatricians, family medicine physicians, and immunization nurses at medical centers that had the highest and lowest HPV vaccine completion rates within the same health care system. Results: In both groups, almost all providers reported strong support for the HPV vaccine. In detailing how they talk to parents and patients about the vaccine, more of the providers working at higher completion centers described using effective communication techniques, including engaging parents and patients in two-way conversation and demonstrating awareness of cultural and practical barriers to completion that families may face. Providers at higher completion centers were also more likely to depict a local medical culture supportive of and committed to HPV vaccine completion, with greater levels of proactivity and teamwork. In contrast, providers working at lower completion medical centers described a lack of proactivity, and the strategies they suggested to improve HPV vaccine completion tended to be approaches that someone other than medical providers would implement. The comments made by these providers sometimes reflected a level of negativity and judgment absent from the comments of providers at higher completion centers. Conclusion: Interventions to improve HPV vaccination completion rates should address both individual- and system-level factors. Improving communication skills, encouraging a supportive medical culture, and addressing resource issues is likely to improve vaccine adherence.